Enhancing ferro-nanofluid performance in wavy minichannels: Investigating entropy generation and vorticity under magnetic field influence - Bhadri, Anshuman; Singh, Harvindra; Ranjan Pati, Pravat; Chamoli, Sunil; Kishore, Chandra; Sharma, Vishal; Chadge, Rajkumar; Kanan, Mohammad (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This work examines how channel shape and magnetic field strength influence heat transfer characteristics in magneto-hydrodynamic (MHD) systems. Five different channel geometries were analyzed under magnetic field intensities ranging from 1200 G to 2500 G and Reynolds numbers between 50 and 250. The properties of local flows, vorticity patterns, and entropy formation were examined using numerical simulations. The findings demonstrate that stronger magnetic fields improve heat transfer efficiency, while higher field strengths produce more intricate entropy and vorticity patterns. Heat transfer efficiency is influenced by channel geometry; Case 3 outperforms the others and exhibits the highest levels of vorticity and entropy formation. In all geometries, it was discovered that entropy formation increased with magnetic field strength and decreased with rising Reynolds number. The study also shows that there is a trade-off between flow resistance and heat transfer enhancement, with configurations that generate the highest levels of vorticity and entropy typically exhibiting greater friction factors. Entropy values ranged from 225.67 to 593.26 under different situations and scenarios, with Case 2 showing the highest sensitivity to parameter changes. For a variety of technological applications, these findings provide crucial insights for optimizing MHD-based heat transfer systems and directing the development of efficient thermal management solutions. Heat transmission efficiency is influenced by the form of the channel. While Cases 4 and 5 had more consistent but weaker patterns, Case 3 exhibited the highest vorticity and generated the highest entropy, suggesting higher heat transmission capabilities.